Analisis Sistem Pengendalian Intern Pemerintah (SPIP) terhadap Pendistribusian Bantuan Sosial Covid-19 di Dinas Sosial Provinsi DKI Jakarta Tahun 2020 - Orce Kabunggul; Yeni Husnaeni; Kumba Digdowiseso (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2023)
The aim of the study was to find out how the Government Internal Control System (SPIP) performs in the implementation of Covid-19 income assistance at the DKI Jakarta Provincial Social Service according to the Elements of Internal Control based on PP No. 60 of 2008 concerning the Government Internal Control System (SPIP). This study uses a qualitative method with an interpretive paradigm and an ethnomethodological approach. Data collection techniques for this study were through interviewing key informants and supporting informants, observation and documentation. Based on the results of this study, the implementation of the SPIP in the implementation of income assistance in the implementation of the Covid-19 countermeasures has generally been effective and sufficient in accordance with Government Regulation No. 60 of 2008. Therefore, additional and evaluation is still needed. Implementation, such as discussing ethics and ethics training, assessing the role of assistants and social workers and identifying risks, was not carried out due to the risk of delays in the distribution schedule. Keywords: Government Internal Control System, Covid-19 Social Assistance, SPIP